Recovery of Palladium and Rhodium from Spent Automotive Catalytic Converters - ZAKERI, M.; NADERI, H. (Asian Journal of Chemistry, 2010)
Platinum group metals recovery from spent automotive catalysts is new issue in Iran. Recovery of palladium and rhodium from spent automotive catalytic converters using HCl + NHO3 as oxidising agents was investigated. Effects of temperature, leaching time and solid/liquid ratio were studied. Optimum conditioned were determined at temprature 90 ºC, time 4 h and solid content 100 g/L. Maximum palladium and rhodium extractions were 1.756 and 0.145 g/kg cat., respectively.